The active site structure of heme a33+ C N CuB2+ of cytochrome aa3 oxidase as revealed from resonance raman scattering - Pinakoulaki, Eftychia; Vamvouka, Magdalini; Varotsis, Constantinos (My University, 2003)
Resonance Raman and FTIR spectroscopies have been employed to investigate the structure of the heme a3-C≡N-CuB complex of oxidized cytochrome aa3 oxidase. The characterization of this complex is essential since a central issue in the physiological function of cytochrome oxidase is the extent to which the partially reduced dioxygen substrate interacts with the two metals. The resonance Raman spectra display two isotope-sensitive vibrational modes at 488 and 406 cm-1. The FTIR spectrum displays one isotope-sensitive mode at 2151 cm-1. We assign the peak at 488 cm-1 to the Fe-C≡N-CuB stretching mode, the peak at 406 cm-1 to the Fe-C≡N-Cu B bending mode, and the peak at 2151 cm-1 to the C≡N stretching mode. The comparison between the data on CN-bound oxidized enzyme and the data on model compound 1 illustrates that changes in the both the Cu-N≡C angle and NCN-Cu stretch will influence the overall frequency of Fe-CN, while a decrease in the Cu-N-C angle will decrease the triple bond character of bridging cyanide
Keywords: Heme; Cyanides; Enzymes; Fourier transform infrared spectroscopy